2019
DOI: 10.1186/s42408-019-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Dendrochronological reconstruction of fire history in coniferous forests in the Monarch Butterfly Biosphere Reserve, Mexico

Abstract: Background: Some have proposed that fire return intervals lengthen with elevation in montane tropical coniferous forests, such as those found in central Mexico. This would generate patterns of synchronous tree establishment in higher elevation forests dominated by Abies sp. Mill., and patterns of continuous tree establishment in lower elevation forests dominated by Pinus sp. L. However, it is common to find codominant stands of both genera at intermediate elevations. The Monarch Butterfly Biosphere Reserve (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…Fire history studies conducted in central Mexico have documented uninterrupted fire frequencies up until the early part of the 21st century [26,48,49,56], while others have documented fire exclusion after 1970 [49]. Our results suggest the frequency of widespread fires changed after 1983 (Figure 3C).…”
Section: Fire Frequenciesmentioning
confidence: 56%
See 2 more Smart Citations
“…Fire history studies conducted in central Mexico have documented uninterrupted fire frequencies up until the early part of the 21st century [26,48,49,56], while others have documented fire exclusion after 1970 [49]. Our results suggest the frequency of widespread fires changed after 1983 (Figure 3C).…”
Section: Fire Frequenciesmentioning
confidence: 56%
“…These results address the first research question and are similar to results from other mixed conifer studies that include Abies species [51] in the southwestern United States and northern Mexico, which generally found that fire occurred once per decade before the current fire suppression period. Relatively short mean fire intervals of five years were also found in mixed conifer stands that included Abies in the states of Chihuahua [25], Durango [24], Michoacán and Mexico [26]. In addition, many of the fire years recorded within A. religiosa forests were synchronized with fire years in adjacent P. hartwegii forests located less than 5 km away [47].…”
Section: Fire Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlecht et Cham) and smooth-bark Mexican pine (Pinus pseudostrobus Lindley) are two conifer species widely distributed in temperate forests in central Mexico. Field-based observations and two recent fire chronologies confirm the possibility of reconstructing fire regimes by analyzing fire scars in trees of both species (Sáenz-Ceja and Pérez-Salicrup 2019b;Cerano-Paredes et al 2021). However, little is known about the characteristics of fire scars in samples obtained from the two species, information that could be useful when conducting field sampling in dendroecological research.…”
Section: Introductionmentioning
confidence: 91%
“…These are relict forests from the last glaciation period and host high pine species diversity (Farjon 1996). Most of the reconstructed fire regimes have focused on pine species (Yocom and Fulé 2012;Cerano-Paredes et al 2015;Sáenz-Ceja and Pérez-Salicrup 2019b). In contrast, studies on other conifers, such as the Abies species, are very few in these ecosystems because it has been assumed that these experience standreplacement fires (Rodríguez-Trejo 2008), and forest legacies decay quickly owing to moist conditions (Moreno-Valdez et al 2018).…”
Section: Introductionmentioning
confidence: 99%